Evaluation of Takayasu's arteritis activity by ultrasound localization microscopy. (3rd October 2022) - Goudot, G; Jimenez, A; Mohamedi, N; Sitruk, J; Khider, L; Mortelette, H; Tanter, M; Messas, E; Pernot, M; Mirault, T
Abstract: Objectives: Use of sulphur hexafluoride microbubbles (MB) with ultrasound can provide arterial wall enhancement. The use of ultrafast imaging with MB super-localization offers the possibility of ultrasound localization microscopy (ULM) and thus a visualization of in vivo carotid vasa vasorum. We aim to perform in vivo Vasa vasorum imaging in the carotid wall in Takayasu's arteritis and to provide a correlation with the disease's activity. Methods: Patients with Takayasu arteritis were consecutively included in the national referral centre. Assessment of activity was performed by NIH activity index, with measurement of biological inflammation, morphological evaluation by computed tomography (CT) angiography, and 18-fluorodeoxyglucose CT scan. Ultrafast ultrasound imaging was performed with a 7 MHz central frequency linear probe. A dedicated contrast imaging sequence (plane waves with 8 angles, frame rate 500 Hz, voltage 8 V, duration of 8 s), coupled with the intravenous injection of sulphur hexafluoride MB allow us to store the raw radio frequency data of the MB passage. After a pre-processing step to accumulate frames properly including a frames selection and a movement correction, the MB were localized then tracked, allowing reconstruction of the vasa vasorum. The inflammation was quantified through MB tracked and normalized for inter acquisition comparison. Results: 16 patients were included. 5 patients (median age 35.8 [24.5–46.0] years, 3 women) had active disease and 11 patients (37.2 [31.7–47.3] years, 9 women) had quiescent disease. The passage of MB allowed the visualisation of microvessels within the arterial wall for active cases. The number of MB detected per second in the wall was 118 [80–169] for active cases vs. 13 [10–15] for quiescent cases (p=0.0005). Conclusion: ULM allows visualization of microvessels within the carotid wall, with significantly greater MB passage in active Takayasu arteritis. ULM provides for the first time a precise visualization in vivo of the vasa vasorum and gives access to quantification of the vascularity of the arterial wall. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Société française de cardiologie